Relationship Between Enthusiasm in Teaching and Teacher Turnover in Public Secondary Schools in Bushenyi Ishaka Municipality, Uganda - Tukahirwa Evas Bindeeba; Tukur Muhammad; Lucy Aja; Alex Behakanira Tumwesigye (Journal of Research in Education and Pedagogy, 2025)
Teacher enthusiasm, defined as the integration of positive emotional experiences—such as enjoyment in teaching—with their outward expression through observable behaviors, is widely recognized as a vital attribute of effective and high-quality instruction. Although research on teacher enthusiasm has a long tradition within educational psychology, much of it has predominantly emphasized teachers’ external manifestations during instruction, including voice, tone, facial expressions, and body movements or gestures. The present study explores the relationship between enthusiasm in teaching and teacher turnover in public secondary schools in Bushenyi – Ishaka Municipality, Uganda. Specifically, it assesses the extent to which enthusiasm in teaching relates to teacher turnover in public secondary schools in Bushenyi-Ishaka Municipality. The research design was a cross-sectional design. A mixed-approach research approach, which blends quantitative and qualitative methods within a single study, was used. The population size was 4454, and the sample size used was 367 respondents selected randomly but proportionately depending on the number of teachers and students using Sloven’s formula. The instruments used for data collection were questionnaires and interview guides. The collected quantitative data were analyzed using Pearson correlation and multiple regression analysis with the aid of SPSS software version 27.0. Qualitative data were thematically analyzed. The reliability of 0.872 was established using the Cronbach formula. Frequencies, means, and percentages were also employed. The findings revealed a strong negative correlation between teaching enthusiasm (TE) and teacher turnover (TT), with a correlation coefficient of -0.789 (p < 0.05), indicating that higher teacher enthusiasm is associated with lower turnover rates. The multiple regression analysis showed that motivation contributes significantly to teacher turnover, explaining 64.5% of the variance (R² = 0.645). The model underscores the importance of teacher enthusiasm in reducing turnover rates. Therefore, teachers who demonstrate high enthusiasm for their work are more likely to stay in their positions, leading to a reduction in teacher turnover. Given the above findings, it is recommended that educational leaders prioritize the development of supportive teaching environments. By focusing on these areas, schools can improve teacher satisfaction and retention, ultimately leading to a more stable and effective educational setting for students.